Production And Properties Of ‘Buluh Semantan’ (Gigantochloa Scortechinii Gamble) Hardboard Compared To Commercially Produced Pine Hardboard - Salim, Sabiha (2007)

(untitled)
Bamboo, a fast-growing plant with great versatility is being manufactured into various products of wood composites. In Malaysia, Buluh Semantan (G. scortechinii Gamble) is the most commercially utilised bamboo species and currently, fast being studied on its anatomical, physical and mechanical properties for contribution towards expanding the bamboo industry. Another potential product utilising bamboo fibre is hardboard, due to its long fibres produced good fibre bonding and strong hardboard. A study was conducted to determine the potential of utilizing bamboo (Gigantochloa scortechinii) for hardboard production. The objective of this study were to prepare and evaluate the bamboo fibre after undergone pre-treatment processes prior to refiner mechanical pulping (RMP), to determine the optimum pre-treatment process for fibre production, and to evaluate the mechanical and physical properties of hardboard from bamboo compared to those of commercial hardboard from pine. Bamboo chips were either treated by soaking in 2% (w/v) sodium hydroxide (NaOH) solution at 60ºC for 4, 6 and 8 h or by steaming at 170ºC at 5.95 kgcm-2 pressure for 3 h to soften them. The results showed that chips pre-treated with NaOH yielded higher fibre recovery (77.2%) compared to those of steamed (50.7%). Fibre recovered from NaOH pre-treatment produced more unbroken fibres than those of steam. Fibre after undergone steam pre-treatment produced darker fibres compared to those of NaOH treated. Thus, from these measurements of fibre recovery and morphology, fibre from NaOH pre-treated produced better fibre quality than those of steam-treated. It was also found that soaking in 2% NaOH for 6 h was the most optimum treatment condition for the bamboo fibre. Thirty 3-mm hardboards (density, 1000 kgm-3) prepared from the pre-treated fibres of bamboo, with and without resin and additives were then fabricated. Phenol formaldehyde (PF) resin at two concentration levels, i.e., 1% and 2% (based on oven dry weight of board), wax emulsion at 1% and 2% (based on oven dry weight of board), and alum (Al2(SO4)3) at 0.25% (based on oven dry weight of board) were added selectively to enhance the properties of the boards. Boards were hot pressed at 1800C for 20 min and tempered in a forced circulation oven at 1600C for 6 h. Physical and mechanical properties of the boards were evaluated in accordance with Japanese Industrial Standard for Fibreboard (JIS A 5305-2003). Properties of commercial hardboard made from pine of the same thickness were also tested for comparison purposes. The results showed that all bamboo hardboards produced from NaOH pre-treated fibres showed higher Modulus of Rupture (MOR) and Modulus of Elasticity (MOE) values compared to the commercial hardboard. NaOH pre-treated board with 2% PF resin+1% wax and 2% PF resin+2% wax had the highest bending strength values (MOR values) but poor in dimensional stability compared to the commercial hardboard. Bamboo hardboards without resin and additives produced from steam-treated fibres showed lower MOR and IB values compared to those produced from NaOH pre-treated fibres. The bamboo hardboards without resin and additives showed lower MOR and Internal Bond (IB) values compared to those with resin and additives. Increasing PF resin and wax levels of concentration from 1% to 2% had increased the strength and stiffness properties of bamboo hardboards; namely the MOR, MOE and IB and was significant at p<0.01. The Internal Bond (IB) value showed the highest for hardboard with 2% PF resin+2% wax though was lower than the commercial hardboard (1.64 and 1.92, respectively). Bamboo hardboard was superior in terms of bending strength when compared to the commercially produced hardboard. Meanwhile for dimensional stability, bamboo hardboards showed poorer resistant to water absorption (WA) than the commercial and the value did not meet the JIS Standard specified.